Tonisitas dalam Sample Intonasi Dialog Spontan Bahasa Jawa Ngoko: Sebuah Kajian Sistemik Fungsional - Eni Suryati (Balai Bahasa Provinsi Papua, 2019)
This paper proposes to study tonicity (the placing of tonic syllable) in a spontaneous dialog in Javanese Ngoko. Ngoko is one of the three speech levels in Javanese, viz. Krama (formal, bonorific), Madya (mid), and Ngoko, the lowest level (Poedjosoedarmo, 1979). Javanese is a regional language of Indonesia.In the framework of Systemic Functional Linguistics, Halliday (1994) classifies tonicity as one of the systems in intonation. Tonicity identifies an obligatory element in information unit, i.e. new element. It is new because it is not recovable from the context. In identifying tonicity, Halliday (1970) claims that although it is usually congruent with the most salient syllable, the most important property of it is the major range of pitch when compared to the surrounding syllables within a tone group.By using the recorded spontaneous dialog in Javanese Ngoko, we examine tonicity in the intonation. PRAAT analysis is used to look at the pitch movement by observing the fundamental frequency (F0). Segmentation is syllable in PRAAT text grid allows us to read carefully the range of pitch for all syllables. This grounds the claim of tonicity in a tone group along with the reading of its context. Intensity, characterizing whether one syllable is more salient than another, is observed to find out if the tonic syllable is always the most salient one. Duration is also observed to add the phonetic value of the tonic syllable.It is significant to notice that in term of intonation, Systemic Functionalist look at it as the integral part of the grammar. Hence, trinocular vision (from above, roundabout and below) is mantained. From above, the intonation is the realization of information structure in the lexicogrammar stratum. From roundabout within the phonology stratum, there is choice of placing tonic syllable and of tone. From below, the phonetic evidence supports the choice. The discussion in this paper, then, is limited on the acoustic phonetic evedence of placing the tonic syllable. The choice of tonic syllable in relation to the information structure in terms of new element is discussed with the context derived from the natural speech exchanges in the dialogue. Whenever neccessary, the discussion on the thematic structure is also provided to look at the interaction between the two structures (Information and Thematic) within the context.